Determinants of Caesarean Section in Bangladesh: A Multilevel Analysis of BDHS 2017-2018 Data - Haque, M Ershadul; Sharmin, Sabina; Sharmin, Sayema (Dhaka University Journal of Science, 2023)
In recent years Caesarean Section (C-S)is considered as an important mode of child delivery in lowering mother and infant mortality. However, the unnecessary use of C-S has detrimental impacts on both mothers’ and newborns’ health. The purpose of this study is to evaluate the prevalence of caesarean delivery and to find out the related factors influencing the rapid rise in C-Sin Bangladesh by considering an appropriate statistical model in line with the data structure. The study is based on the data from the 2017-2018 BDHS which is a nationally representative survey. BDHS is conducted periodically and 2017-2018 is the latest of all the BDHS conducted so far. Information used in the present study was collected from 5230 mothers who provided complete information about all the variables considered in the study. Among the Bangladeshi women, the rate of Caesarean sections (C-S) was reported to be 32.94% which is high in any international standard. Multilevel analysis suggests that the highest education level, current working status, wealth index, media exposure, number of decisions in which women participated, age at birth, BMI, birth order of the index child, number of ANC visits during the period of pregnancy, and childbirth weight have significant influence on whether mothers deliver babies through the C-S. In order to prevent needless caesarean deliveries and safeguard mothers from the consequences, Bangladesh urgently needs caesarean delivery policy guidelines. The study will help the policymaker in taking such initiatives. Dhaka Univ. J. Sci. 71(2): 117-126, 2023 (July)